O depoimento da testemunha: a "retórica do povo" sobre um sumário julgamento sem júri - Allyson Afonso Alves Pereira (2019)
Our purpose with this dissertation is to investigate the argumentation in a criminal case that deems a crime of homicide committed by police officers. Our intention is to understand how the witness constructs the argument in his testimony. To do so, we develop our work from theArgumentative Discourse Analysis theory, seeking to find the doxa and the doxical elements that support this discursive enunciation produced by a "people of the people" within the web that forms the legal discourse. Amossy (2007, 2011 and 2018), Perelman & Olbrechts-Tyteca(1996) and Lima (2006, 2009, 2011, 2013 and 2017), among others, are used as theoretical reference on argumentation. Thus, we seek to understand how the argumentative functioning of the testimony works, looking for traces that may corroborate with a possible relativizationof Human Rights, in addition to seeking social representations about the PMMG and favela residents. We intend to analyze how these representations intertwine with the practices of police violence in places of social exclusion. We also used Agamben's research (1993, 2004 and 2007) to help us understand the non-application of law in the situations of violence present in our case, so that we can delineate how cultural discursive practices reflect the social situation of abandonment state-owned.